1993
DOI: 10.1016/0140-6736(93)92992-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep paralysis

Abstract: Sleep paralysis is a common condition with a prevalence of 5-62%. Although most affected people have single or infrequent episodes, sleep paralysis may be recurrent, or occur in association with the narcoleptic syndrome. In a study of 22 subjects with frequent sleep paralysis and also excessive daytime sleepiness, episodes continued for between 5 and 35 years. In contrast to subjects with the narcoleptic syndrome, these patients did not have cataplexy, daytime sleepiness and insomnia were less severe, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 9 publications
1
62
2
2
Order By: Relevance
“…SP occurs most commonly in women (Pires et al, 2007;Sharpless and Barber, 2011) and when the body is in supine position (Chilcott et al, 1998;Sharpless etal., 2010). The prevalence of SP among the general population is controversial, ranging from 5 to 62% (Dahlitz & Parkes, 1993). In a sample of nearly two thousand Canadian university students, Spanos et al (1995) found that 21% of these subjects experienced SP; however, in this sample there was no significant inter-gender difference.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…SP occurs most commonly in women (Pires et al, 2007;Sharpless and Barber, 2011) and when the body is in supine position (Chilcott et al, 1998;Sharpless etal., 2010). The prevalence of SP among the general population is controversial, ranging from 5 to 62% (Dahlitz & Parkes, 1993). In a sample of nearly two thousand Canadian university students, Spanos et al (1995) found that 21% of these subjects experienced SP; however, in this sample there was no significant inter-gender difference.…”
Section: Introductionmentioning
confidence: 99%
“…Cheyne & Girard (2009) consider that out-of-body experiences and SP hallucinations have different neurobiological basis. Dahlitz & Parkes (1993) speculate that a lack of synchrony between changes in brain activity and muscle atonia is the mechanism responsible for bodily immobilization during SP.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations